IMPULSE VS INTENT: A BEHAVIOURAL STUDY ON ONLINE SHOPPING TRIGGERS AMONG COLLEGE STUDENTS - T. Manoj Kumar; G. Venkadasalapathy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the impact of marketing stimuli, website design, and emotional states on impulse and intentional purchases among college students in online shopping. The findings show that promotions and discounts are the most effective drivers of both types of purchases, with product recommendations also having a significant, but smaller, influence. Positive emotions mediate the relationship between discounts and impulse purchases, highlighting the importance of emotional engagement. While website design factors like visual appeal and navigation ease showed minimal direct effect on purchase Behaviour, a cluster analysis identified two consumer segments one responsive to aggressive marketing and another preferring personalized strategies. These insights suggest that retailers should focus on promotions, personalized recommendations, and emotional engagement to effectively target both impulse and intentional buyers, optimizing sales and customer satisfaction.